Optimum Layout of Multiple Tree-type Boreholes in Low-Permeability Coal Seams to Improve Methane Drainage Performance - Zhang, Liang; Qi, Qingjie; Deng, Kai; Zuo, Shaojie; Liu, YingJie (Frontiers in Energy Research, 2021)
Extracting coal mine methane (CMM) is important for underground mining safety. The tree-type borehole drainage (TTBD) technique can effectively remove methane from coal seams. Determining a suitable drilling pattern for multiple tree-type boreholes will promote the efficient application of this technique in coal mines. Aimed at solving the problem that the optimum methane extraction layout for multiple tree-type boreholes is unclear, this study first constructed a full-coupled thermo-hydro-mechanical model to simulate methane flow in coal. This model and data from a coal mine were used to investigate the effect of multiple tree-type borehole layouts, tree-type borehole spacing, different Langmuir volume and different Langmuir pressure constants, and initial coal permeabilities on CMM drainage. The results show that the different tree-type borehole layouts result in significant differences in drainage and that the use of a rhombic sub-borehole layout can reduce the methane pre-drainage time by up to 44.4%. As the tree-type borehole spacing increases, the total time required for pre-drainage increases as a power function. As the Langmuir pressure constant, the fracture permeability, or the matrix permeability increases, the effective drainage zone expands. The effective drainage zone also expands when the Langmuir volume constant decreases but all these changes are accompanied by a shortening of the drainage completion time. These results can provide a reliable basis for optimizing tree-type borehole drilling layouts.